Factors that determine the entrepreneurial intention of university students: a gender perspective in the context of an emerging economy - Ada Gallegos; Alejandro Valencia-Arias; Victoria Del Consuelo Aliaga Bravo; Renata Teodori de la Puente; Jackeline Valencia; Hernán Uribe-Bedoya; Verónica Briceño Huerta; Luis Vega-Mori; Paula Rodriguez-Correa (Cogent Social Sciences)
Research on entrepreneurial intention has gained notable ground in the field of entrepreneurship, especially among university students, who represent the potential to become future entrepreneurs. In recent years, a special approach has emerged that has captured the attention of re-searchers: the comparison of entrepreneurial intentions between men and women, highlighting the existing entrepreneurial gap. This study was carried out with the objective of analyzing the factors that determine the entrepreneurial intention of entrepreneurial students, both female and male, from a comparative perspective in Peru. To achieve this, a quantitative analysis was carried out based on the Partial Least Squares Structural Equation Model (PLS-SEM), which integrated the Theory of Planned Behavior (TPB) and the Business Event Model (SEE) with a survey of 1006 students. university students. The results revealed that men have a higher entrepreneurial intention compared to women, being more influenced by factors such as current behavior control, personal attitude, and social support. On the other hand, women showed a greater influence of factors related to control and personal attitude towards entrepreneurship.